A rare case of Takotsubo cardiomyopathy in post cesarean female - Chhabra, Jaya; Bhadoriya, Manjulata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Takotsubo cardiomyopathy, commonly known as stress cardiomyopathy or broken heart syndrome, is a temporary heart condition predominantly occurring in post-menopausal females. It is usually preceded by an intense psychological or physical experience. This is a case report presenting a 32-year-old G3P2L2 patient at 41 weeks of gestation who was diagnosed with this condition shortly after her cesarean.